A Dynamic Rural-Urban-Natural Environment Interactive Spatial Model of Palangkaraya City in Indonesia - Yuzuru Miyata; Hiroyuki Shibusawa (European Regional Science Association (ERSA), 2014)
Permana and Miyata (2009) showed a partial equilibrium urban economic model to explain the existence of illegal settlements in flood prone areas in Palangkaraya City in Central Kalimantan Province, introducing the expected damage rate on household asset. Applying this new idea, one can derive the conclusion where the bid rents by low income households get higher than those by high income households in flood prone areas. This is the contrary conclusion being highlighted as compared with that in the traditional urban economics. Following this paper, Permana and Miyata (2009) extended the partial equilibrium model into a general equilibrium model. And then Permana and Miyata (2009) developed a two dimensional city model applying Miyata's achievement (2009). However the study region, Palangkaraya City and its surrounding area, shows a complicated interaction between natural environment and human activities. Therefore this article aims at developing a rural and urban economic model with natural environment considerably extending our previous literature.
Keywords: O18; Q56; R13; 330; flood damage; natural environment; urban economics